Minimização do cabeçalho do protocolo de comunicação IPV6 visando a melhoria de desempenho em redes locais - Torrel, Robert (2013)
One of the major advances that has been happening in the use of communication technologies, is the gradual replacement of IPv4 by the IPv6. This change provides several enhancements, although the transmission performance is relatively low, by considering the new addressing standard, which becomes 128 bits in IPv6, compared to 32 bits in IPv4, increasing the size of the resultant header and the communication overhead. This work has as main objective the development of a method for the minimization of the IPv6 header, seeking to increase the performance of data transmission in a local area network. Practical tests have shown that the proposed solution enables an improvement in network performance, increasing data throughput, in addition to decreasing latency and bandwidth utilization in the transmission of packets between two devices.